2006
DOI: 10.1111/j.1468-1331.2006.01213.x
|View full text |Cite
|
Sign up to set email alerts
|

Color vision and macular recovery time in epileptic adolescents treated with valproate and carbamazepine

Abstract: Visual dysfunction has been reported in patients diagnosed with epilepsy. Some of these visual disturbances may be attributable to either the disease process, or the anticonvulsant therapy prescribed to control the seizures. The aims of our study were to evaluate whether color vision and macular function are impaired in epileptic adolescents, to study if the monotherapy with valproic acid (VPA) and carbamazepine (CBZ) can affect color vision and macular function and to determine the possible relationship betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 40 publications
0
6
0
1
Order By: Relevance
“…It has been observed a rare transient adverse effect immediately after ECT [3] and general anaesthesia. Antiepileptic drugs are known to result in visual disturbances, particularly colour vision defects [4].…”
Section: Discussionmentioning
confidence: 99%
“…It has been observed a rare transient adverse effect immediately after ECT [3] and general anaesthesia. Antiepileptic drugs are known to result in visual disturbances, particularly colour vision defects [4].…”
Section: Discussionmentioning
confidence: 99%
“… 28 , 29 However, abnormal color visions in epileptic adolescents treated with VPA were reported. 30 , 31 Sisk 7 reported three cases with complications of VPA treatment, two of which had severe decrease in BCVA; the two patients were 8 years and 15 years of age and received 10 mg/kg/d of VPA for 4–5 months. Bhalla et al 8 reported that 12 (39%) of 31 VPA-treated patients reported systemic side effects, of whom nine (29%) discontinued VPA intake due to side effects.…”
Section: Discussionmentioning
confidence: 99%
“…В исследовании A. Verrotti et al нарушения цветовосприятия были выявлены у 13 пациентов (81,25%), принимавших вальпроевую кислоту: у 7 (43,75%) наблюдались отклонения преимущественно в восприятии сине-зеленой части спектра, у 6 (37,5%) -сине-желтой части [38]. В другой работе A. Verrotti et al было показано, что после 1 года терапии данным препаратом сумеречное зрение, по данным никтометрии, сохраняется в пределах нормы [40].…”
Section: другие препаратыunclassified